Guest Editor foreword. Issue 3 (3rd August 2015) - Yuanhui Li, Prof. John Ferguson, Professor; Li, Yuanhui; Ferguson, John
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of the papers included in this issue is to cover a broad range of contemporary issues in Chinese corporate financial management and therefore provide the readers with important insights into Chinese financial markets as well as the social and economic consequences of firm behavior in the Chinese context. Design/methodology/approach – The first part of this issue is a special section on "Corporate Finance and Corporate Social Responsibility", which includes three papers that explore various aspects of corporate social responsibility (CSR) from a finance perspective – including the relationship between CSR and the cost of equity, the "insurance-like effect" of CSR and competition in corporate philanthropy. The remainder of the issue includes seven further papers that cover a wide range of finance-related topics, including currency and equity, monetary policy, cross-border mergers and acquisitions, earnings management, overseas investment, information disclosure, social capital and cosmopolitanism. All of the papers included in this issue are based on empirical research that draws on primary and secondary data from Chinese financial markets and from the information disclosures of Chinese enterprises. Findings – The authors are confident that such in-depth discussions and analysis will help researchers and practitioners to develop a better understanding of the issues faced by Chinese managers in the context of China's economic transformation. The findings reported in this issue will help inform and develop Chinese management theories based on a wide range of Chinese management practices. Originality/value – Each paper in this issue reports on different aspects of finance, reporting and management in the Chinese context, discussing findings that have both relevance and significance beyond China.